Genetic modulation of Valencia sweet orange field performance by 50 rootstocks under huanglongbing-endemic conditions - Bowman, Kim D.; McCollum, Greg; Seymour, Danelle K. (Frontiers in Plant Science, 2023)
Although the citrus scion cultivar primarily determines the characteristics of the fruit, the rootstock cultivar of the graft combination has a major role in determining the horticultural performance of the tree. The disease huanglongbing (HLB) is particularly devastating to citrus, and the rootstock has been demonstrated to modulate tree tolerance. However, no existing rootstock is entirely suitable in the HLB-endemic environment, and citrus rootstocks are particularly challenging to breed because of a long life cycle and several biological characteristics that interfere with breeding and commercial use. This study with Valencia sweet orange scion documents the multi-season performance of 50 new hybrid rootstocks and commercial standards in one trial that forms the first wave of a new breeding strategy, with the aim of identifying superior rootstocks for commercial use now, and mapping important traits to be used in selection for the next generation of outstanding rootstocks. A large assortment of traits were quantified for all trees in the study, including traits associated with tree size, health, cropping, and fruit quality. Among the quantitative traits compared between rootstock clones, all except one were observed to have significant rootstock influence. Multiple progeny from eight different parental combinations were included in the trial study, and significant differences between parental combinations of the rootstocks were observed for 27 of the 32 traits compared. Pedigree information was integrated with quantitative trait measurements to dissect the genetic components of rootstock-mediated tree performance. Results suggest there is a significant genetic component underlying rootstock-mediated tolerance to HLB and other critical traits, and that integration of pedigree-based genetic information with quantitative phenotypic data from trials should enable marker-based breeding approaches for the rapid selection of next-generation rootstocks with superior combinations of traits that are needed for commercial success. The current generation of new rootstocks included in this trial is a step toward this goal. Based on results from this trial, the new hybrids US-1649, US-1688, US-1709, and US-2338 were considered the four most promising new rootstocks. Release of these rootstocks for commercial use is being considered, pending the evaluation of continuing performance in this trial and results from other trials.